UPAYA MENINGKATKAN ACADEMIC SELF EFICACY DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING DI SMK NEGERI 3 SURAKARTA - Nurhayati, Ika; Wardani, Dewi Kusuma; Totalia, Salman Alfarisy (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2015)
The purpose of this research is to improve the academic self-efficacy and learning outcomes class X Marketing 3 SMK Negeri 3 Surakarta academic year 2014/2015 through the application of learning models Discovery Learning. The type of this research is classroom action research. The Subject of this research is student at class x marketing 3 of vocational high school 3 surakarta I the academic year of 2014/2015 with 31 students. The procedures of this research are (a) planning, (b) action, (c) observation, and (d) reflection. Based on the results of the research, the learning process with the implementation of the model of discovery learning can improve academic self-efficacy and learning outcomes of students. This was evident in the first cycle of academic self-efficacy of students in terms of indicators - indicators of academic self-efficacy increased by 25.85% (percentage prasiklus namely 40.62 and 66.45 in the first cycle). The study of students also experienced an increase in the amount of 6.5% (the average value of pre-cycle learning outcomes 70.18 and 76.68 the first cycle) In the second cycle of academic self-efficacy of students continues to increase, as evidenced by indicators - indicators of academic self-efficacy increased 17:42%. The study of students in the second cycle also experienced an increase in the amount of 8:14% and the percentage of completeness increased 12.9% (the percentage of first cycle and cycle II 80.64 93.54%).